Extraction and stability of bixin from the seeds of Annato (Bixa orellana L.) - Pe, Janet E.; Acevedo, Teresita P. (1983.)
This study primarily involved the extraction of bixin which is the principal coloring matter of annatto seeds and the determination of its stability as food color. A preliminary study was made to determine the optimum extracting condition of bixin from annatto. Four-gram samples of annatto seeds were weighed and heated in 40 ml corn oil and propylene glycol separately at 125°C for 10, 20 and 30 minutes. From the absorbance readings, bixin extracted using propyleneglycol had a higher specific wavelength (630 mu) than the one using corn oil where the maximum absorbance reading was observed at 530 mu. Of the three heating periods employed, heating for 30 minutes showed the highest absorbance reading. For the storage study of the pigment, annatto extracts stored at elevated temperatures (50-55°C) showed the lowest stability at all pH levels used. Of the different pH levels employed, corn oil extract stored at a higher pH level (6.7) appeared to be more stable than when stored at pH 4.9 and 3.6. For propylene glycol extract, samples stored at a lower pH level (pH 3.4) had the greatest stability as compared with those stored in pH 4.3 and 5.8.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Annato